2013
DOI: 10.1186/bcr3483
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor class B type I regulates cellular cholesterol metabolism and cell signaling associated with breast cancer development

Abstract: IntroductionPrevious studies have identified cholesterol as an important regulator of breast cancer development. High-density lipoprotein (HDL) and its cellular receptor, the scavenger receptor class B type I (SR-BI) have both been implicated in the regulation of cellular cholesterol homeostasis, but their functions in cancer remain to be established.MethodsIn the present study, we have examined the role of HDL and SR-BI in the regulation of cellular signaling pathways in breast cancer cell lines and in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
145
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 55 publications
11
145
0
Order By: Relevance
“…The second mechanism is based on the capacity of SR-B1 to trigger an intracellular signaling cascade that leads to increased tumor cell proliferation. In this regard, activation of the PI3K/AKT pathway by SR-B1 ligands provides an essential survival signal for tumor cells [84,85]. A third mechanism of SR-B1 to promote tumor growth is by the inhibition of acute inflammation [73,74].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second mechanism is based on the capacity of SR-B1 to trigger an intracellular signaling cascade that leads to increased tumor cell proliferation. In this regard, activation of the PI3K/AKT pathway by SR-B1 ligands provides an essential survival signal for tumor cells [84,85]. A third mechanism of SR-B1 to promote tumor growth is by the inhibition of acute inflammation [73,74].…”
mentioning
confidence: 99%
“…SR-B1 has been implicated in several biological processes such as apoptosis [86,87] entry through TRPC3 channels, leading to dampened cytokine production in response to CpG via TLR9 activation [90]. Disrupting SR-B1 function by genetic or chemical inhibitors may decrease tumor cell malignancy [85,91]. The main mechanisms of action proposed for these therapeutic interventions are the reduced availability of cholesterol and the decreased activation of the PI3K/AKT pathway.…”
mentioning
confidence: 99%
“…Multiple studies have found that SR-BI is implicated in the regulation of diverse tumor cell biology, including tumor cell proliferation, apoptosis, migration and invasion (7,8). The present study analyzed the expression of SR-BI in multiple gastric adenocarcinoma specimens and found that SR-BI immunoreactivity was present in 69% of cases.…”
Section: Discussionmentioning
confidence: 88%
“…Pronounced expression of SR-BI was observed in a variety of carcinomas, including hepatoma, prostate, breast, colorectal, pancreatic, ovarian, and nasopharyngeal cancer (9)(10)(11)(12). Moreover, SR-BI has been demonstrated to exert a profound influence on the proliferation, migration and invasion of breast and prostate cancer cells (7,8). In human stomach, Lobo et al (13) reported that SR-BI was not detected in epithelial, parietal, mucous and endocrinal cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation